O nadużyciach w badaniach nad doświadczeniem Zagłady - Leociak, Jacek (Zagłada Żydów. Studia i Materiały, 2010)
Abuses in art, film and literature portraying the Holocaust have finally been discussed in modern human studies. The analyses show, among others, the phenomenon of the McDonaldization of the Holocaust, its political intrumentalization,ideological manipulation and commercialization. The article tries to look critically at a different dimension of the phenomenon, hitherto undiscussed, namely the abuses in Holocaust research. The author identifies several dangers which appearin academic discourse about the Holocaust – from “the myth of sources” to narcissistic temptations.